Comparative study of Foley’s catheter and prostaglandin E2 gel for pre-induction cervical ripening - Shetty, Shruti J; J C, Spandana; Arpana, Anju; Sathyanarayana, Chaitra (Asian Journal of Medical Sciences, 2022)
Background: Induction of labor is a crucial and customary clinical procedure in obstetrics. It is arguably one of the most abused procedures. Cervical ripening determines the success of delivery. The availability of newer oxytocics and induction techniques which are simpler and also more predictable has significantly modified our traditionally conservative attitude toward induction of labor. Aims and Objectives: The objective of this study was to determine the effectiveness of Foleys catheter against prostaglandin E2 (PGE2) gel for pre-induction cervical ripening. Materials and Methods: Women attending hospital for induction of labor, with a Bishop’s score <6, were allocated randomly to Foley’s group (Group F) and PGE2 gel group (Group P). Fifty women were allocated to Foley’s group (Group F) and 50 were allocated to gel group (Group P). The Foley’s group had a number 18 Foley catheter inserted into cervix, bulb inflated and placed on traction. Further augmentation was done, after Foleys extrusion or 6 h after gel, either with PGE2 gel or oxytocin solution depending on Bishops score. Results: The Foley’s group had significantly higher change in Bishop’s score (3.12 vs. 2.66, P=0.04). The Foleys group required lesser number of further doses of gel as compared to gel group. No differences were found between the two groups with respect to induction to delivery interval, mode of delivery, non-reassuring fetal heart rate patterns, or baby weight. Conclusion: Foleys catheter was associated with greater change in Bishops score as compared to intracervical PGE2 gel. It was not associated with any side effect during induction process.